Desain Armrest dan Fasilitas Footcycling dalam Pengembangan Kursi Roda sebagai Alat Rehabilitasi Penderita Stroke - Alfan Faiz Hidayatullah; Anda Iviana Juniani; Dhika Aditya Purnomo (Proceedings Conference On Design Manufacture Engineering And Its Application, 2018)
Every year more than 36 million people worldwide die from non- communicable diseases or 63% of all deaths. The cause is cardiovascular disease stroke and coronary heart disease. In Indonesia itself according to the diagnosis of Nakes in 2013 estimated that 2,137,941 people affected by stroke. According to some experts who argue that appropriate therapy for stroke patients in addition to exercise can also run with cycling. In Indonesia, there is no wheelchair for rehabilitation in accordance with anthropometry and community needs. It needs a breakthrough innovation concept of wheelchair design in accordance with fungtion for rehabilitation to keep right position of hand and training foot muscle accordance with the wishes and anthropometri of indonesia society. The method for performing this static bike design analysis is the Ulrich method for the process of design concepts and the RULA method for bicycle ergonomic analysis. The design of static bike is done by anthropometri analysis, ergonomic analysis and strength analysis by using CATIA software. The resulting design based on user rehabilitation needs has several additional functions and components such as armrest, footcycling, and pedal safeguard. With the addition of these functions and components, will further maximize the rehabilitation process of stroke patients in wherever and whenever